Hitchcock [videorecording (DVD)] - Gervasi, Sacha; Hopkins, Anthony, 1937-; Mirren, Helen; Collette, Toni; Johansson, Scarlett, 1984-; Huston, Danny, 1962-; Biel, Jessica, 1982-; Stuhlbarg, Michael; Wincott, Michael, 1959-; Smith, Kurtwood, 1943-; Elfman, Danny; Rebello, Stephen (20th Century Fox Home Entertainment, 2013)
Plagued by both a reckless ego and nagging self-doubt, Hollywood legend Alfred Hitchcock becomes obsessed with a grisly murder story that the studios won't back. Determined, he risks his reputation, his home, and even the love of his wife Alma as he sets out to make the film. Ultimately, Hitch wins Alma over, and the two collaborate to create an enduring masterpiece: Psycho.